2018
DOI: 10.12911/22998993/79417
|View full text |Cite
|
Sign up to set email alerts
|

Successive Methods for the Separation of Titanium Oxide from the Black Sands of Ecuador

Abstract: The black sands found on certain Ecuadorian beaches present a high ilmenite contents up to 50%. In this work, TiO 2 was obtained from the black sands of Muisne beaches -Ecuador by combining the thermal, chemical and ion exchange treatments. For the thermal treatment, the raw material was smelted at temperature of 1100 °C using a basic flux. Subsequently, the chemical treatment was initiated in the presence of Fe 0 metal using chemical digestion with HCl, and the sample was purified by separating the precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Team F reviewed the composition of black sands and their conventional uses in different countries. The students found that the joint presence of iron and titanium oxides naturally could be valued in adsorbents' formulation for removing contaminants with applications in the textile industry [63] and the oil and gas industry [37]. They reviewed statistical data from resource bases of black areas on some beaches of Ecuador.…”
Section: The Circular Economymentioning
confidence: 99%
“…Team F reviewed the composition of black sands and their conventional uses in different countries. The students found that the joint presence of iron and titanium oxides naturally could be valued in adsorbents' formulation for removing contaminants with applications in the textile industry [63] and the oil and gas industry [37]. They reviewed statistical data from resource bases of black areas on some beaches of Ecuador.…”
Section: The Circular Economymentioning
confidence: 99%
“…[9][10][11] One of the safety problems of LiBs is that the separator will shrink or melt at high temperature, leading to the internal short circuit of LiBs, which will release a lot of heat instantaneously, resulted in LiBs fire or explosion. [12][13][14] The common strategy is to modify the surface of the separator with inorganic particles, such as ceramics [15,16] and titanium oxide, [17,18] which are highly thermal stabile in order to improve the thermal resistance of the separator. However, the compatibility of inorganic particles with separator is usually poor.…”
Section: Introductionmentioning
confidence: 99%